ANALISIS KRIMINOLOGI TERHADAP PENCURIAN DATA PRIBADI DI ERA DIGITAL: STUDI KASUS KEBOCORAN DATA PENGGUNA APLIKASI MYPERTAMINA TAHUN 2023 - Irvin Atara; Sharron Syallomeita; Raffi Aqil Baihaqi Haksoro (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study analyzes the data breach of MyPertamina users in May 2023, with a focus on the criminological implications of cybercrime in Indonesia. The incident highlights systemic vulnerabilities in personal data management, which represent not only a technical failure but also a reflection of the weaknesses in national cybersecurity policies. This data breach is identified as a broader threat to the country’s digital sovereignty and national economic stability, with over 44 million lines of sensitive data exposed. The research employs classical criminological theories, such as cyber space theory and routine activity theory, to analyze the contributing factors, motivations of the perpetrators, and the existing system vulnerabilities. Findings emphasize that although investigative efforts have been made, the government’s response has been delayed and ineffective in addressing the evolving cyber threats. The study also provides recommendations to strengthen personal data protection policies and enhance cybersecurity infrastructure through a situational approach and regulatory reinforcement. Overall, this research contributes significantly to understanding the dynamics of cybercrime in Indonesia and urges the development of more adaptive policies to safeguard citizens’ data in the digital era.